Short Synthetic β‐Sheet Antimicrobial Peptides for the Treatment of Multidrug‐Resistant Pseudomonas aeruginosa Burn Wound Infections. Issue 7 (30th January 2017) - Zhong, Guansheng; Cheng, Junchi; Liang, Zhen Chang; Xu, Liang; Lou, Weiyang; Bao, Chang; Ong, Zhan Yuin; Dong, Huihui; Yang, Yi Yan; Fan, Weimin
Abstract : Pseudomonas aeruginosa is often implicated in burn wound infections; its inherent drug resistance often renders these infections extremely challenging to treat. This is further compounded by the problem of emerging drug resistance and the dearth of novel antimicrobial drug discovery in recent years. In the perennial search for effective antimicrobial compounds, the authors identify short synthetic β‐sheet folding peptides, IRIKIRIK (IK8L), IRIkIrIK (IK8‐2D), and irikirik (IK8D) as prime candidates owing to their high potency against Gram‐negative bacteria. In this study, the peptides are first assayed against 20 clinically isolated multidrug‐resistant P. aeruginosa strains in comparison with the conventional antibiotics imipenem and ceftazidime, and IK8L is demonstrated to be the most effective. IK8L also exhibits superior antibacterial killing kinetics compared to imipenem and ceftazidime. From transmission electron microscopy, confocal microscopy, and protein release analyses, IK8L shows membrane‐lytic antimicrobial mechanism. Repeated use of IK8L does not induce drug resistance, while the bacteria develop resistance against the antibiotics after several times of treatment at sublethal doses. Analysis of mouse blood serum chemistry reveals that peptide does not induce systemic toxicity. The potential utility of IK8L in the in vivo treatment of P. aeruginosa ‐infected burn wounds is further demonstrated in a mouse model. Abstract : Short synthetic β‐sheet forming peptides demonstrate potent efficacy against 20 strains of difficult‐to‐treat clinically isolated multidrug‐resistant P. aeruginosa . Repeated use of the peptide does not induce drug resistance. The peptide IRIKIRIK mediates rapid bactericidal activity and efficiently eradicates bacteria in an in vivo P. aeruginosa infected mouse burn wound model, leading to enhanced survival rate with no systemic toxicity.